1999
DOI: 10.1161/01.cir.99.11.1471
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Weight and Rate of Increase in Weight During Childhood and Adolescence to Body Size, Blood Pressure, Fasting Insulin, and Lipids in Young Adults

Abstract: Background-Weight gain is of concern during early development because adult obesity and its cardiovascular consequences appear to have their origins during childhood. Insulin resistance is known to be related to obesity. Thus, weight gain beginning in childhood may influence the development of insulin-induced cardiovascular risk during adulthood. Methods and Results-We monitored 679 individuals from 7.7Ϯ0.1 years of age with repeated measures of height, weight, and systolic blood pressure (SBP) until 23.6Ϯ0.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
238
4
11

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(267 citation statements)
references
References 51 publications
12
238
4
11
Order By: Relevance
“…Of the eight studies considering the relationship between childhood BMI and adult blood pressure (27)(28)(29)(30)(31)(32)(33)(34) , six showed positive associations (27)(28)(29)(32)(33)(34) . However, when adjusted for adult BMI, only two associations remained positive (32,33) and four studies demonstrated significant negative associations (i.e.…”
Section: Independent Effects Of Childhood Obesity On Adult Disease Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the eight studies considering the relationship between childhood BMI and adult blood pressure (27)(28)(29)(30)(31)(32)(33)(34) , six showed positive associations (27)(28)(29)(32)(33)(34) . However, when adjusted for adult BMI, only two associations remained positive (32,33) and four studies demonstrated significant negative associations (i.e.…”
Section: Independent Effects Of Childhood Obesity On Adult Disease Riskmentioning
confidence: 99%
“…Similarly the data were mixed for TAG in the unadjusted data sets (28)(29)(30)41) , but only negative associations were reported for data sets adjusted for BMI (29,30) . Three out of six (28)(29)(30)(42)(43)(44) studies looking at insulin concentrations or resistance showed a positive association with childhood BMI (28,29,42) , but these were again attenuated or reversed with adjustment for BMI. Similarly to the cardiovascular outcomes, the two studies using older adult cohorts showed negative relationships with childhood BMI (30,43) .…”
Section: Independent Effects Of Childhood Obesity On Adult Disease Riskmentioning
confidence: 99%
“…3 Weight increases during adolescence have also been associated with fasting insulin, HDL-cholesterol, and systolic blood pressure in young adulthood. 4 Furthermore, childhood and adolescent obesity are significant predictors of overweight status in adulthood [5][6][7] and pose a risk factor for adult morbidity and mortality, particularly for males. 8,9 The recent Surgeon General's 'Call to Action' 10 describes overweight and obesity as a public health epidemic, with specific focus on the impact of overweight for children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is associated with elevated levels of fasting insulin and lower insulin sensitivity. [3][4][5] In obese adults, ghrelin concentrations are lower than in normal weight control subjects. 6,7 Weight loss led to an increase of plasma ghrelin in adults and children.…”
Section: Introductionmentioning
confidence: 99%